THE EFFECT OF THE SHOW AND TELL METHOD ON STUDENTS VOCABULARY SKILLS AT THE TENTH GRADE OF SMKS RAKSANA 2 MEDAN - Winda Damanik; Nurhayati Sitorus; Christina Natalina Saragi (Jurnal Basataka (JBT), 2025)
This research examines a critical issue in English language proficiency among tenth-grade students at SMKS Raksana 2 Medan, particularly those in the Automation and Office Governance (OTKP) program who demonstrate low vocabulary skills despite the school's emphasis on English competency for vocational purposes. The research addresses whether the Show and Tell (S&T) Method affects students' vocabulary skills, with the primary objective of determining this method's impact on vocabulary acquisition for grade X OTKP students. Employing an experimental approach, the study will compare vocabulary skills between students taught using Show and Tell versus traditional methods, assessing knowledge through pre- and post-tests focused on nouns related to office administration, equipment, and activities relevant to the OTKP curriculum. The anticipated results are expected to demonstrate significant improvement in vocabulary skills among students exposed to the Show and Tell Method, suggesting its effectiveness for enhancing vocabulary acquisition in a vocational school context. Based on the data analysis by using t-test, it was found that Tcount was 3.62 at 5% significant level, and the Ttable was 2.048 it means that Tcount > Ttable. It means that H0 was rejected and Ha was accepted. It means that The Show And Tell Method significantly affects vocabulary skills, at the 10th grade OTKP (Office Automation and Governance) SMKS Raksana 2 Medan.